Pengaruh Kesadaran Wajib Pajak, Pelayanan Fiskus, dan Sanksi Administrasi Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor Menggunakan Metode Mix Method (Pada Kantor Pelayanan Pajak Kendaraan Bermotor Samsat Kota Yogyakarta) - Ramadhan, Rizki; Binawati, Enita (Jurnal Solusi, 2020)
Tax is the main source of state revenues where the activity of countries such as national development funded by tax. National development funded is difficult to do if there is no revenue from tax sector. To make the effectiveness of development equity, decentralization from the central government to supervise and arrange directly about affairs in the regions is needed that policy, planning, implementation, and financing are given to the regional government. The purpose of this research is to find the influence of the awareness of taxpayers, the quality of services, and the tax penalty toward taxpayers compliance. The method used in this research is explanatory research. Accidental sampling technique is used by spreading questionnaires to one hundred taxpayers vehicles registered in samsat tax office of Yogyakarta. Besides spreading the questionares writer did an interview to the responden so that in this research writer use mix method. The research result indicates that awareness taxpayers have a positif impact toward the compliance of taxpayers’ motor vehicles registered in samsat tax office of Yogyakarta and quality of services, and tax penalties have a negatif impact toward the compliance of taxpayers’ motor vehicles registered in samsat tax office of Yogyakarta.